Effect of Peat Water Mix with Borehole Water on Mortality of African Catfish - Ardianor Ardianor; Tutwuri Handayani; Noor Syarifuddin Yusuf; Rosana Elvince (Universitas Gadjah Mada, 2022)
Generally, cultured fish are suitable in media with a pH of around 7, like mountainous river and borehole water. However, peat water is known with low pH. It is not suitable for fish culture, especially for fingerlings. This study was conducted to examine the survival of African catfish fingerling (Clarias gariepinus) in the mixture of peat and borehole water with different pHs. Survival test of African catfish as subject applied bioassay method, LC50-96 hours. Peat water as the agent was arranged for 11 concentration levels of 0% - 100% with no replication and placed in plastic basins with 20 liters each. Catfish fingerlings were used for subject fish (size 10-15 cm) and 10 individuals in each basin. Water quality, mortality, and behavior of fish were observed. Results showed that the survival ability of African catfish on peat water, the LC50-96 hours was 63.8%, with 95% CI between 53.3% and 76.4% in concentration. Behavioral response of fish fingerling exposed to peat water ≥ 40% in the beginning 2 hours was frequently swimming up to surface. Lethal responses fingerlings were frequently taking up oxygen to the water surface, horizontally swimming, and moving vertically before death. After death, the fish ran out of mucus, and the skin looked peeling and bruising.